71 The Effect of Different Bones and Analytical Method on Assessment of Bone Mineralization Response to Dietary P, Phytase and Vitamin D in Nursery Pigs. (12th April 2022) - Williams, Hadley; Chin, Taylor; Gebhardt, Jordan T; Tokach, Mike D; Woodworth, Jason C; DeRouchey, Joel M; Goodband, Robert D; Bergstrom, Jon R; Rahe, Michael; Siepker, Christopher; Sitthicharoenchai, Panchan
Abstract: Three hundred-fifty pigs (initially 11.9±0.56 kg) were used to evaluate effects of different bones and analytical methods on assessment of bone mineralization response to dietary P and vitamin D in nursery pigs. Pens of pigs (5 pigs/pen) were randomized to 6 dietary treatments in a randomized complete block design with 10 pens/treatment. After feeding diets for 28-d, 8 pigs/treatment were harvested for bone analysis. Treatments were: 1) P at 0.19% STTD P (deficient), 2) P at 0.33% STTD P (NRC requirement) using monocalcium phosphate, 3) P at 0.33% STTD P including phytase, 4) P at 0.44% STTD P (industry level) using monocalcium phosphate, phytase, no vitamin D, 5) diet 4 with vitamin D (1, 653 IU/kg), 6) diet 5 with additional 2, 000 IU/kg 25(OH)D3 (HyD). Final BW, ADG, and ADFI increased linearly ( P < 0.05) and G:F improved (quadratic, P < 0.05) as P increased. The response to treatment for bone density and ash was dependent upon bone (density×bone interaction, P = 0.044; non-defatted bone ash×bone interaction, P = 0.060; defatted bone ash×bone interaction, P = 0.068). Pigs fed 0.19% STTD P had decreased ( P < 0.05) bone density and ash (non-defatted and defatted) for all bones compared with 0.44% STTD P, with 0.33% STTD P generally intermediate or similar to 0.44% STTD P. Pigs fed 0.44% STTD P with no vitamin D had greater ( P < 0.05) non-de-fatted fibula ash compared with all treatments other than 0.44% STTD P with added HyD. Pigs fed the 3 diets with 0.44% STTD P had greater ( P < 0.05) de-fatted 2 nd rib ash compared with pigs fed 0.19% STTD P or 0.33% STTD P with no phytase. In summary, bone density and ash responses varied depending on bone. Differences in bone density and ash in response to vitamin D and P were most apparent with fibulas and 2 nd ribs.